Bridge to health informatics—a 5-week intensive online program to increase diversity in health informatics - Howard, Angelita P.; Slaughter, Liane Siu; Simmonds, Consuela; McPherson, Rebecca; Kennedy, Nia; Bentley, Keisha (Frontiers in Education, 2023)
Introduction Health informatics (HI) has the potential to address health disparities and improve healthcare outcomes; however, lack of diversity in the workforce, especially at advanced levels, feeds disparities, and creates inequities. Increasing participation from underrepresented minorities requires exposure and connection to the field and career opportunities including advanced degrees. Morehouse School of Medicine (MSM) created the no-cost, 5-week intensive online Bridge to Health Informatics (B2HI) program in 2021 to connect participants from backgrounds underrepresented in HI with industry-relevant skills, professional certification, business experience, and graduate training opportunities. Methods The curriculum included intensive training in knowledge and current trends, business propositions, and professional certifications. Successful completion of the B2HI provided scholars with guaranteed admissions into the Master of Science in Health Informatics (MSHI) degree program, which premiered at MSM in August 2021. We deployed several strategies to attract individuals interested in advancing their careers in HI. To assess the impact of the recruitment strategy and program, we analyzed applicant demographics, the interests of those accepted into the program, and feedback from participants via anonymous online surveys. Results In 2021, our recruitment efforts attracted 65 applications, over whom 90% self-identified as African American and the majority were working adults. Among the 46 applicants accepted and enrolled, 38 (83%) completed the program. Thirteen B2HI graduates enrolled in the first offerings (Fall 2021 and Spring 2022) of the online MSHI degree program, the highest number for the first sessions of our online master’s degree programs, indicating that B2HI connects scholars with advanced training. Participants indicated immense overall satisfaction with the program and had strong positive responses for increased interest and confidence to do advanced work in the subject. Discussion The data indicate that B2HI addresses key factors that hinder diversity in healthcare and informatics-related fields, including awareness, access, and social support, and connect students with the next stages of training toward careers that require an advanced degree. By providing opportunity, resources, and networks that help participants raise their potential to become leaders and decision-makers in the healthcare industry, programs like B2HI enable the collective effort to decrease health disparities.